A Study of The Best Selling Smartphone in The Two Biggest Marketplace in Indonesia - Alfian Budi Primanto; M Khoirul ABS; Afi Rahmat Slamet (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2018)
The number of entrepreneurs in Indonesia has increased significantly in the past decade. Many entrepreneurs expand their business into digital by using marketplace platform. Although, there are a lot of entrepreneur use digital landscape to scale up their business, many online business ended in failure. This research aims to answer the following questions; what is the success factor of smartphone campaign in the Indonesia marketplace platform? Is there any difference success factor between each marketplace platform? The researcher uses secondary data, simple random sampling, and binary logistic regression modeling for the purpose to answer research questions. Interestingly, this research shows that there are no relationship between seller reputation and sales acquirement. Also, there is no difference behaviour between each marketplace platform. Therefore, to be succeed in marketplace competition, each seller should pay attention to their price competitiveness while at the same time find the best option to increases their number of store page views.